DETERMINANTS OF LABOR FACTORS IN TRADITIONAL BIRTH ATTENDANTS AT THE EILOGO SABU RAIJUA PUBLIC HEALTH CENTER - Atalia Pili Mangngi; Mery L.Fangidae Tumeluk; Belandina A Nggadas; Brigita Dina Manek (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
A safe and safe delivery is the hope for maternity mothers. Until now, there are still many deliveries carried not in health facilities. This has an impact on increasing MMR and IMR and becoming a health problem in Indonesia. The research design used a cross sectional study approach. The population in this study were all pregnant women who gave birth to traditional birth attendants in 2021 with a total sample of 70 respondents. The measuring instrument uses a questionnaire The results showed that there was a relationship between knowledge (p=0.000), mother's attitude (p=0.000), socio-culture (p=0.001), delivery history (0.002) and social support (0.000) with childbirth at traditional birth attendants in the work area of ​​the puskesmas. Eilogo Sabu Raijua Regency. It is hoped that health workers will further improve services by giving more special attention to every pregnant woman by continuing to provide counseling about safe deliveries assisted by health workers and in health service facilities.